Qualitative analysis of the factors associated with whistleblowing intentions among athletes from six European countries - Toner, John; Jones, Luke; Fairs, Lucas; Mantis, Constantine; Barkoukis, Vassilis; Daroglou, Garyfallia; Perry, John L.; Micle, Andrei V.; Theodorou, Nikolaos C.; Shakhverdieva, Sabina; Stoicescu, Marius; Pompiliu-Nicolae, Constantin; et al. (Frontiers in Sports and Active Living, 2024)
Although whistleblowing is thought to represent an effective mechanism for detecting and uncovering doping in sport, it has yet to become a widely adopted practice. Understanding the factors that encourage or discourage whistleblowing is of vital importance for the promotion of this practice and the development of pedagogical material to enhance the likelihood of whistleblowing. The current study employed a qualitative methodology to explore the personal and organisational factors that underpin intentions to blow the whistle or that may lead to engagement in whistleblowing behaviours in sport. Thirty-three competitive athletes across a range of sports took part in a semi-structured interview which sought to explore what they would do should they encounter a doping scenario. Content analysis revealed that whistleblowing is a dynamic process characterised by the interaction of a range of personal and organisational factors in determining the intention to report PED use. These factors included moral reasoning, a desire to keep the matter "in-house", perceived personal costs, institutional attitudes to doping, and social support. Analysis revealed a number of 'intervening events' (Ajzen, 1991), including a perceived lack of organisational protection (e.g., ethical leadership) within some sporting sub-cultures, which present an important obstacle to whistleblowing. The intention to report doping was underpinned by a "fairnessloyalty trade-off" which involved athletes choosing to adhere to either fairness norms (which relate to a sense that all people and groups are treated equally) or loyalty norms (which reflect preferential treatment towards an in-group) when deciding whether they would blow the whistle. The promotion of fairness norms that emphasise a group's collective interests might encourage athletes to view whistleblowing as a means of increasing group cohesiveness and effectiveness and thereby increase the likelihood of this practice.